Effect of heating temperature on quality of bio-briquette empty fruit bunch fiber - Nofriady Handra; Anwar Kasim; Gunawarman Gunawarman; Santosa Santosa (Institute of Advanced Engineering and Science, 2020)
Empty Fruit Bunches (EFB) are one of the palm oil industry wastes, which are quite plentiful and currently unused optimally. Biomass is one of the renewable energy resources which has important roles in the world. The bio-briquettes are manufactured through densification of waste biomass by implementing certain processes. This research aimed to obtain variations in the mold temperature at 150 ºC, 200 ºC, and 250 ºC to the calorific value and toughness of the briquette material. The toughness was tested using ASTM D 440-86 R02 standard. Arduino program was used for setting the heating resistance time of the mold, which was 20 minutes and the thermal controller was used to adjust the temperature variation. The average mold pressure was 58 Psi. The highest heating value was obtained at a mold temperature of 250 ºC with a value of 5256 cal/g, and the lowest was resulted at a temperature of 150 ºC (4117 cal/g). Meanwhile, the briquette toughness test at 200 ºC mold temperature indicated good data results in which the average loss of fiber particles was only 4.17 %, this was because the adhesion between particles by lignin and cellulose in the fiber functions optimally at this temperature so that the resistance of briquettes went through minor damage.